Ecosystem Metabolism Is the Dominant Source of Carbon Dioxide in Three Young Boreal Cascade‐Reservoirs (La Romaine Complex, Québec). Issue 4 (3rd April 2023) - Barbosa, Pedro M.; Bodmer, Pascal; Stadler, Masumi; Rust, Felipe; Tremblay, Alain; del Giorgio, Paul A.
Abstract: The impoundment of rivers for multipurpose reservoirs has significant consequences to the carbon cycle, one of the most relevant being the increase in greenhouse gases emissions. Reservoirs have been shown to be net sources of such gases to the atmosphere, emitting between 0.8 and 1.08 Pg carbon dioxide (CO2 ) equivalents per year. Even though emission estimates have become common, less is known about the processes driving this CO2 excess, a prerequisite for understanding and ultimately predicting and managing CO2 emissions from reservoirs. In the present study, we aimed at exploring ecosystem metabolism (gross primary production, ecosystem respiration, and net ecosystem production [NEP]) and its environmental drivers in three young hydroelectric reservoirs in a cascade configuration but with distinctive morphometries (shape, depth, and size). By combining our metabolic measurements with a hydrological mass balance approach, we quantified the relative contributions of internal (ecosystem metabolism) versus external sources (tributaries and groundwater) to the reservoir surface diffusive CO2 emissions. There was a predominance of net heterotrophy in all sites, and metabolism played a key role in fueling CO2 fluxes in all three reservoirs, NEP alone being able to account for the measured fluxes in approximately 50% of all sites. Internal production was thus the main process explaining total reservoir CO2 diffusive emissions (∼100%), with groundwater and tributaries contributing similarly but more modestly (∼9% each). Our results contribute to our understanding of the processes underlying boreal reservoir carbon footprints, and in particular, for apportioning the emissions can be attributed to the reservoir itself. Plain Language Summary: Damming rivers for multiple human needs has important effects on the aquatic carbon cycle, being the increase in carbon dioxide (CO2 ) and methane emissions one of the most concerning. Both these gases contribute to global warming, so scientists have focused on estimating their emissions from reservoirs, but little is known about the processes involved in the CO2 excess. Even less information is available from the boreal region, where large hydroelectric projects have been developed. We estimated the contribution of internal (aquatic metabolism) versus external (groundwater and inflowing rivers) CO2 sources to the total CO2 flux in three recently built reservoirs. Aquatic metabolism was the dominant CO2 source in all systems, being able to explain fluxes on more than half occasions. A lower fraction of CO2 comes from groundwater and from rivers that feed the reservoirs, both having a similar contribution. Our results are important to better understand the share of the total CO2 emissions that can be attributed to the building of the reservoir itself and therefore to power generation, an information that is important not only for scientists but also for industry and governments interested in developing more realistic greenhouse gas assessments associated with energy generation. Key Points: Large spatial variability of metabolic rates, with prevalence of heterotrophy in most sites of lakes, reservoirs, and rivers Metabolism has a strong influence on carbon dioxide fluxes, being frequently able to sustain most observed fluxes Tributaries and groundwater were a modest but nonnegligible source of carbon dioxide to all three reservoirs